The growth of the gaming industry in the context of creative industries - Rykała, Piotr (Rozwój sektora gamingu w kontekście przemysłów kreatywnych, 2020)
This paper aims to provide an overview of the studies and literature regarding creative industries, with particular consideration of the video game industry, and define potential areas of further research, among others regarding e-sports. The author seeks to define creative industries, describe the Polish and global video game industries, point to their characteristics and present the development of the Polish and global video game markets providing the examples of the conducted research. The study involves a survey of literature sources, mainly covering the themes related to creative and video game industries, seeks to analyse the global and Polish video game markets based on the data from domestic and international reports
Biblioteka Regionalisty, 2020, Nr 20, s. 124-136
Keywords: creative industries; innovation; computer games; computer games industry; przemysły kreatywne; innowacyjność; gry komputerowe; sektor gier komputerowych